COGNITIVE NATURE OF TRANSLATION ACTIVITY («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The approach to solving the culture-specific problem largely depends on the interpretation of the most basic problem in linguistics - speech and thought, language and thought- speech reciprocity, and at the same time the compatibility of universality and ethnicity, which is considered the first-level issue for translation, as well as the possibilities and methods of transmission of the latter.